EFEKTIFITAS KONSELING KELOMPOK DENGAN RELAXATION TECHNIQUE (TEKNIK RELAKSASI) UNTUK MEREDUKSI MOOD SWINGS (PERUBAHAN SUASANA HATI) BELAJAR SISWA KELAS XL F-2 BOARDING SCHOOL MAN 1 SURAKARTA TAHUN AJARAN 2025/2026 - Zahratul Firdausi, Yasmin; Adi Putro, Eko; Jawandi, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of group counseling services using relaxation techniques in reducing mood swings in learning among students of class XI F-2 Boarding School at MAN 1 Surakarta in the 2025/2026 academic year. The study employed a quantitative approach with a pre-experimental design using a One Group Pretest-Posttest Design. The research subjects consisted of 10 students of class XI F-2 Boarding School at MAN 1 Surakarta selected through purposive sampling. The research instrument was a mood swings questionnaire that had been tested for validity and reliability. Data analysis was conducted using the Wilcoxon test with the assistance of SPSS version 23.The results showed a decrease in mood swings scores after the implementation of group counseling with relaxation techniques, with a mean pre-test score of 106.3 and a mean post-test score of 91.9. The Wilcoxon test results indicated a significance value of 0.005 < 0.05, thus it can be concluded that group counseling services using relaxation techniques are effective in reducing learning-related mood swings among students of class XI F-2 Boarding School at MAN 1 Surakarta. This study implies that the application of relaxation techniques in group counseling can help students regulate emotions, calm their thoughts, and improve learning concentration.